Lysine‐241 Has a Role in Coupling 2OG Turnover with Substrate Oxidation During KDM4‐Catalysed Histone Demethylation. (6th April 2018) - Hancock, Rebecca L.; Abboud, Martine I.; Smart, Tristan J.; Flashman, Emily; Kawamura, Akane; Schofield, Christopher J.; Hopkinson, Richard J.
Abstract: The JmjC histone lysyl demethylases (KDMs) play important roles in modulating histone methylation states and have the potential to be regulated by oxygen availability. Lys241 of the KDM4 subfamily is proposed to be important in oxygen binding by KDM4A. We report evidence that, although Lys241 is unlikely to be directly involved in oxygen binding, it has an important role in coupling 2‐oxoglutarate cosubstrate oxidation with lysine demethylase activity. The results suggest that compounds promoting the uncoupling of substrate oxidation are of interest as JmjC‐KDM inhibitors. Abstract : Keeping active : The JmjC histone lysyl demethylases (KDMs) play important roles in modulating histone methylation states and have the potential to be regulated by oxygen availability. Biochemical analyses reveal that Lys241 in KDM4 promotes the coupling of 2‐oxoglutarate oxidation with demethylation activity, thus ensuring efficient catalysis and avoiding enzyme inactivation.